Factores explicativos de la demanda de calidad en el servicio de las empresas de transporte público de pasajeros en el distrito de Laredo - 2015 - Pizarro Vásquez, Lourdes de la Caridad (2017)
The purpose of this research is to explain the factors that determine the quality of public transport in Laredo. Depending on the scope of the investigation, it has opted for a non-experimental, transversal and descriptive design - correlational. It was considered population to public transport users residing in the district of Laredo. It was designed and implemented a data collection instrument based on 377 surveys made directly to the people who use public transport from Laredo to move to their places of work or study or meet their household activities. By using the method of binary logistic regression, it was determined because of an investigation that the explanatory factors for user satisfaction are the way of handling and treatment of users.